1998
DOI: 10.1191/026765898674095369
|View full text |Cite
|
Sign up to set email alerts
|

Phonological transfer and levels of representation: the perceptual acquisition of Thai voice and aspiration by English and French speakers

Abstract: In this article, we show that the generative phonological distinction between lexical and surface representation can explain apparently contradictory orders of acquisition of L2 voice and aspiration contrasts by native speakers of English. Cross-language speech perception research has shown that English speakers distinguish synthetic voice onset time counterparts of aspirated–unaspirated minimal pairs more readily than voiced–voiceless. Here, we present evidence that in the perceptual acquisition of the same T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 17 publications
2
40
1
Order By: Relevance
“…This is in striking contrast with most of the studies reviewed in the first paragraphs of this introduction, namely Curtin et al (1998), Pallier et al (2001) and Hayes-Harb and Masuda (2008), all of which provide evidence that is consistent with homophonous lexical entries for L2. The present study aims to answer the question of how L2 learners can establish contrastive lexical representations for phonemes that they do not reliably discriminate in listening tasks.…”
Section: Introductioncontrasting
confidence: 90%
“…This is in striking contrast with most of the studies reviewed in the first paragraphs of this introduction, namely Curtin et al (1998), Pallier et al (2001) and Hayes-Harb and Masuda (2008), all of which provide evidence that is consistent with homophonous lexical entries for L2. The present study aims to answer the question of how L2 learners can establish contrastive lexical representations for phonemes that they do not reliably discriminate in listening tasks.…”
Section: Introductioncontrasting
confidence: 90%
“…In the field of SLA, studies have reported that learners transfer VOT values from the L1 into the L2, both in perception (e.g. Curtin et al 1998, Pater 2003 and in production (e.g. Flege et al 1998, Suomi 1980.…”
Section: Adult L2 Acquisition Of An Aspirating Languagementioning
confidence: 99%
“…For example, Stager and Werker (1997) found that although 14-month-old infants could discriminate a minimal pair contrasting /b/ and /d/, they failed to learn to use these phonetically similar sounds in a word-object association task. In adult sound-to-word learning, Curtin et al (1998) found that subjects' error pattern associated with perceiving a newly learned phonetic contrast depended on whether the experimental task required what they called ''lexical access.'' In addition, Samuel (2002) argued that lexical knowledge can influence phoneme identification.…”
Section: Neural Bases Of Speech and Word Learning In Adultsmentioning
confidence: 99%
“…In terms of behavioral studies, we are aware of one that examined the learning of a foreign segmental contrast (Thai voicing and stop consonants) and its contribution to word learning (Curtin et al, 1998). In terms of learning suprasegmental contrasts in words (phonetic features that are not associated with consonants or vowels and occur in most languages of the world), we have recently developed a training program investigating the learning of pitch patterns in word identification by native English-speaking adults (Wong and Perrachione, in press).…”
Section: Sound-to-word Learningmentioning
confidence: 99%